Androgen induced cellular proliferation, neurogenesis, and generation of GnRH3 neurons in the brain of mature female Mozambique tilapia. Issue 1 (December 2018) - Narita, Yasuto; Tsutiya, Atsuhiro; Nakano, Yui; Ashitomi, Moe; Sato, Kenjiro; Hosono, Kohei; Kaneko, Toyoji; Chen, Ruo-Dong; Lee, Jay-Ron; Tseng, Yung-Che; Hwang, Pung-Pung; Ohtani-Kaneko, Ritsuko
Abstract The neuroplastic mechanisms in the fish brain that underlie sex reversal remain unknown. Gonadotropin-releasing hormone 3 (GnRH3) neurons control male reproductive behaviours in Mozambique tilapia and show sexual dimorphism, with males having a greater number of GnRH3 neurons. Treatment with androgens such as 11-ketotestosterone (KT), but not 17β-estradiol, increases the number of GnRH3 neurons in mature females to a level similar to that observed in mature males. Compared with oestrogen, the effect of androgen on neurogenesis remains less clear. The present study examined the effects of 11-KT, a non-aromatizable androgen, on cellular proliferation, neurogenesis, generation of GnRH3 neurons and expression of cell cycle-related genes in mature females. The number of proliferating cell nuclear antigen-positive cells was increased by 11-KT. Simultaneous injection of bromodeoxyuridine and 11-KT significantly increased the number of newly-generated (newly-proliferated) neurons, but did not affect radial glial cells, and also resulted in newly-generated GnRH3 neurons. Transcriptome analysis showed that 11-KT modulates the expression of genes related to the cell cycle process. These findings suggest that tilapia could serve as a good animal model to elucidate the effects of androgen on adult neurogenesis and the mechanisms for sex reversal in the fish brain.